2011
DOI: 10.1063/1.3662143
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigations of elastic stability and electronic structure of cubic platinum carbide under pressure

Abstract: The authors have presented a detailed investigation on the phase stabilities and electronic properties of ideal stoichiometric platinum carbide (PtC) in the rock-salt (RS) and zinc-blende (ZB) structures under high pressure. Theoretical calculations are performed using the first-principles pseudopotential density functional method, in which we employ the generalized gradient approximation (GGA) of the Perdew-Burke-Ernzerhof form and local density approximation (LDA) of Ceperly and Adler parameterized by Perdew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
9
1
1
Order By: Relevance
“…Through the analysis of energy-volume variation, we find that the TcC in the NaCl structure is the ground-state phase, and it is contrary to the research results of Sun et al [6][7][8] who reported that the ZnS structure is more stable phase and the NaCl structure is a high-pressure phase for PtC. In fact, most of the transition-metal monocarbides usually crystallize in the cubic NaCl structure [16].…”
Section: Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Through the analysis of energy-volume variation, we find that the TcC in the NaCl structure is the ground-state phase, and it is contrary to the research results of Sun et al [6][7][8] who reported that the ZnS structure is more stable phase and the NaCl structure is a high-pressure phase for PtC. In fact, most of the transition-metal monocarbides usually crystallize in the cubic NaCl structure [16].…”
Section: Introductioncontrasting
confidence: 67%
“…Their accurate first-principle calculations indicate that the recently synthesized compound PtC is crystallized in the ZnS structure at zero pressure and that the NaCl structure is a high-pressure phase, which the phase transition studied from the usual condition of equal enthalpies occurs at the pressures of 46.6 and 46.5 GPa for GGA and LDA calculations, respectively. In spite of this, the whole set of elastic constants calculated for not only ZnS-but also NaCl-PtC [6][7][8] is all fulfilled the stability criteria for the cubic crystal: ,c 11 > 0, c 44 > 0, and c 11 þ 2c 12 > 0 [9]. From this sense, the synthesized PtC in Ref.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…С теоретической точки зрения, в последнее время было проведено боль-шое количество расчетов для предсказания структурных, когезионных, электронных, механических и т. д. свойств этих материалов [2]. Следует отметить, что большинство этих работ посвящено стехиометрическим (C/M = 1) монокарбидам MC, для которых обсуждалась сравни-тельная стабильность их различных гипотетических по-лиморфов, см., например, [2,[11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionunclassified
“…Elastic constant may be the most important mechanical quantity in that the elastic constants of a solid relate to various fundamental solid state properties such as interatomic potentials, equation of state, phonon spectra [30]. Most importantly, knowledge of elastic stiness coecients is essential for many practical applications related to the mechanical properties of a solid.…”
Section: Elastic Propertiesmentioning
confidence: 99%